Heterosis for grain yield and its attributing traits in bread wheat (Triticum aestivum L.) - Dudhat, Hilay; Pansuriya, Ashwin; Vekaria, Deep; Dobariya, Hardik; Patel, Jagdish; Singh, Chandrakant; Kapadiya, I B (Journal of Cereal Research, 2022)
The present investigation was undertaken in order to estimate the heterosis for grain yield and its components in bread wheat (Triticum aestivum L.) for 13 characters. The crosses were attempted by using line × tester mating design among 8 lines and 4 testers during rabi 2019. The resultant 32 hybrids together with 12 parents and 1 standard check (GW 451) were tested using randomized block design with three replications at Wheat Research Station, Junagadh Agricultural University, Junagadh during rabi 2020-21. The prominent heterotic effects were observed for grain yield per plant and its components. A total of 3 and 3 hybrids exhibited significant desirable heterobeltiosis and standard heterosis, respectively for grain yield per plant. The heterobeltiosis for grain yield ranged from -47.58 % to 62.72 %, while standard heterosis ranged from -35.06 % to 36.92 %. The cross J 16-08 × GW 366 (62.72%) exhibited the highest desirable heterosis over better parent followed by J 16-08 × GW 11 (28.98%) and J 17-08 × GW 366 (19.39%). The cross J 16-08 × GW 366 (36.92%) exhibited highest significant heterosis towards positive direction over standard check, followed by J 16-08 × GW 11 (17.36%) and GW 513 × GW 11 (11.58%). These hybrids also exhibited desirable heterosis for important yield attributes suggesting that the heterosis for grain yield was associated with heterosis for component characters.